1993
DOI: 10.1182/blood.v81.2.446.bloodjournal812446
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of a receptor for hyaluronan-mediated motility on normal and malignant B lymphocytes

Abstract: Migration through extracellular matrix is fundamental to malignant invasion. A receptor for hyaluronan-mediated motility (RHAMM) has previously been shown to play a fundamental role in locomotion of ras- transformed cells as well as functioning in signal transduction. Expression of RHAMM was characterized on B lymphocytes from normal and malignant lymphoid tissues using multiparameter phenotypic immunofluorescence analysis as well as functional analysis of its role in locomotion of malignant hairy cell leukemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…VLA-5) and the expressed a401 integrin, while for formula-fed children, 7 5 4 0 % expressed a high density of a 4 p l and 40-50% expressed a661 (29). This apparent activation of B cells was confirmed by the expression of RHAMM, a receptor for hyaluronan-mediated motility, absent from normal B cells (20,21) but readily detectable on 30-50% of B cells from formula-fed children. Thus based on several measures, unlike PBMC from breastfed children, T and B cells from children fed formula appear to circulate in a chronically activated state.…”
Section: Discussionmentioning
confidence: 78%
“…VLA-5) and the expressed a401 integrin, while for formula-fed children, 7 5 4 0 % expressed a high density of a 4 p l and 40-50% expressed a661 (29). This apparent activation of B cells was confirmed by the expression of RHAMM, a receptor for hyaluronan-mediated motility, absent from normal B cells (20,21) but readily detectable on 30-50% of B cells from formula-fed children. Thus based on several measures, unlike PBMC from breastfed children, T and B cells from children fed formula appear to circulate in a chronically activated state.…”
Section: Discussionmentioning
confidence: 78%
“…5). MN Thy were cultured for 3 days on wells coated with MoAbs to ␤ 1 -, ␣ 4 -or ␣ 5 -integrins followed by extraction of RNA and detection of RHAMM-specific mRNA using a RHAMM cDNA probe [36]. The inhibition of RHAMM-specific mRNA by all three MoAbs confirmed that the absence or reduction of staining for surface RHAMM reflected an inhibition of mRNA expression and thus a genuine loss of RHAMM from the cell surface.…”
Section: Expression Of Rhamm Mrna Is Inhibited By Moabs To ␤ 1 ␣ 4 mentioning
confidence: 87%
“…Northern analysis of mRNA. RNA extraction, Northern analysis and dot-blots were carried out as previously described [34][35][36], and blots were probed with RHAMM cDNA [16,36].…”
Section: Methodsmentioning
confidence: 99%
“…Cord blood was taken at delivery. Solid tissues were minced and passed through a sieve to disperse cells followed by purification on Ficoll-Paque (Pharmacia, Dorval, Quebec, Canada) [41,42]. Lymphoid cells from bone marrow were flushed from the bone using a syringe to force medium through the bone matrix.…”
Section: Materials and Methods Tissuesmentioning
confidence: 99%